Penatalaksanaan Fisioterapi Pada Kondisi Myofascial Syndrome Upper Trapezius Dengan Modalitas Infra Red (IR), Ultrasound (US), Myofascial Release Technique Dan Contract Relax Stretching - Munaya, Arini Khaira; Prasetyo, Eko Budi (LPPM Universitas Pekalongan, 2023)
Myofascial syndrome is a condition characterized by the presence of a hypersensitive region, called a trigger area of muscle or loose connective tissue, together with a specific pain reaction in the area associated with that point when the Trigger Point (Myofascial Trigger Point) is touched or palpated. This causes a localized seizure response known as the confluence sign, which is a shortening of the fibrous muscle fiber. Physiotherapy examination includes pain assessment with Visual Analogue Scale, muscle spasm with palpation, joint range of motion with goniometer, muscle weakness with Manual Muscle Testing, and functional activity with Neck Disability Index. In this case, the interventions chosen were Infra Red (IR), Ultrasound (US), Myofascial Release and Contract Relax Stretching.The purpose of this study was to determine the effect of Infra Red (IR), Ultrasound (US), Myofascial Release and Contract Relax Stretching on the condition of Myofascial Syndrome Upper Trapezius. The research design used in this research is descriptive analytic method. The subjects of this study were patients with Upper Trapezius Myofascial Syndrome at RSUD Dr. SOESELLO SLAWI. The method of collecting research data was 4 times therapy, it was found a decrease in pain at T3, a decrease in M.Upper Trapezius muscle spasm at T4, an increase in the range of motion of the joint, neck flexion at T2, neck extension at T2, lateral neck flexion at T2, neck rotation at T2, increased strength. muscles in flexors at T2, extensors at T4, latero at T3, rotators at T3.